Functional Magnetic Resonance Imaging in the Olfactory Perception of the Same Stimuli - Ciorba, Andrea; Hatzopoulos, Stavros; Cogliandolo, Cristina; Bianchini, Chiara; Renna, Martina; Perrucci, Luca; Skarzynska, Magdalena; Skarżyński, Piotr Henryk; Campioni, Paolo; Cittanti, Corrado; Carnevale, Aldo; Giganti, Melchiore; et al. (Life (Basel, Switzerland), 2020)
Background. Data in the literature report that a number of studies have attempted to identify the exact location of the cortical olfaction representation, searching for evidence suggesting that sniffing odors can initiate a primary activation of the piriform cortex and the insula. Nowadays, due to the SARS-CoV-2 (COVID-19) outbreak, the functional study of the olfactory system could offer a better understanding of the physiopathology of olfactory perception, elucidating better the possible site(s) of damage induced by the COVID-19 infection. The aim of this paper was to evaluate brain maps generated from functional Magnetic Resonance Imaging (fMRI) data, collected from healthy individuals in response to the same olfactory stimulus. Methods. A total of 45 healthy volunteers, without history and/or no clinical signs of sinonasal disease and without history and/or presence of olfactory dysfunction underwent fMRI assessment. Subjects were presented with the same odorous stimuli at specific intervals. fMRI generated brain maps were used in the identification of different cortical areas, involved in the stimuli perception. Results. The fMRI brain maps showed that odorous stimuli activate primarily the left anterior insula (in 35/45 cases or 77.8%). Other activated areas include: the low temporal gyri, the middle and superior temporal gyri, the frontal and piriform cortex, the anterior cingulate gyrus, the parahippocampal gyrus, the temporopolar area, the para-insular area, the subcentral area, the supramarginal gyrus, the occipital cortex and the cerebellum. Conclusions. fMRI resulted as a safe and reliable means to study the perception of olfaction in the cortex. The data of this study suggest that the anterior insula is the main stimulated area when olfactory stimuli are present. This area is always activated, despite the hand and nostril dominance.